Production of itaconic acid from jatropha curcas seed cake by aspergillus terreus - Ahmed El-Imam, A.M.; Kazeem, M.O.; Odebisi, M.B.; Oke, M.A.; Abidoye, A.O. (University of Agricultural Sciences and Veterinary Medicine (UASVM), Cluj-Napoca, Romania Romanian Academy of Agricultural and Forestry Sciences Horticulture and Forestry Society from Transylvania (SHST), 2013)
Submerged substrate fermentation of Jatropha seed cake, a by-product of oil extraction from Jatropha curcas seed was carried out using Aspergillus terreus for the production of itaconic acid. The Jatropha seed cake was initially converted into fermentable sugars by dilute acid hydrolysis using 50% sulphuric acid. The rate of hydrolysis was 1.04 gL-1. The fermentation process was carried out at room temperature, agitation of 400 rpm and three physico-chemical parameters (pH, inoculum size and substrate concentration) were varied. Itaconic acid and glucose assays were carried out by spectrophotometry and Dinitrosalicylic acid methods respectively daily. Maximum yield of itaconic acid was 48.70 gL-1 at 5 ml of inoculum size, 50% substrate concentration and pH 1.5. The residual glucose concentration increased for the first two days of fermentation after which it began to decrease as the itaconic acid concentration increased. The least concentration of itaconic acid observed was 6.00 gL-1, obtained after 24 hours of fermentation with 4 ml inoculum size, 50% substrate concentration and at pH 1.5. The findings of this work indicate that Jatropha curcasseed cake is a suitable substrate for itaconic acid production.